Correction: Brij-58 template synthesis of self-assembled thermostable lamellar crystalline zirconia via a reflux-hydrothermal hybrid method. Issue 68 (7th July 2016) - Su, Penghe; Gao, Wenjun
Abstract : Correction for 'Brij-58 template synthesis of self-assembled thermostable lamellar crystalline zirconia via a reflux-hydrothermal hybrid method' by Penghe Su et al., RSC Advances, 2015, 5, 36467–36471.